Advances in chitooligosaccharides chemical modifications. Issue 9 (11th June 2021) - Chapelle, Camille; David, Ghislain; Caillol, Sylvain; Negrell, Claire; Desroches Le Foll, Myriam
Abstract: Chitooligosaccharides (COS) differ from chitosan by their molar mass: those of COS are defined to be lower than 20 kg mol −1 . Their functionalization is widely described in the literature and leads to the introduction of new properties that broaden their application fields. Like chitosan, COS modification sites are mainly primary amine and hydroxyl groups. Among their chemical modification, one can find amidation or esterification, epoxy‐amine/hydroxyl coupling, Schiff base formation, and Michael addition. When depolymerized through nitrous deamination, COS bear an aldehyde at the chain end that can open the way to other chemical reactions and lead to the synthesis of new interesting amphiphilic structures. This article details the recent developments in COS functionalization, primarily focusing on amine and hydroxyl groups and aldehyde‐chain end reactions, as well as paying considerable attention to other types of modification. We also describe and compare the different functionalization protocols found in the literature while highlighting potential mistakes made in the chemical structures accompanied with suggestions. Such chemical modification can lead to new materials that are generally nontoxic, biobased, biodegradable, and usable in various applications. Abstract :